2022
DOI: 10.1002/jsfa.12069
|View full text |Cite
|
Sign up to set email alerts
|

Computer‐assisted in vitro reconstitution of purine degradation pathway to lower the purine content in food

Abstract: BACKGROUND With the increasing prevalence of gout and its etiological hyperuricemia, dietary control of gout based on low‐purine food according to patients' eating habits is becoming a better choice compared to the existing drug treatment such as allopurinol with notorious side effects. Reconstructing the purine metabolic pathway in vitro to degrade purine substances in food into natural functional allantoin appears to be an innovative method for preparing nutritious and healthy food of low purine content. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…In addition, product inhibition of XOD also has been reported ( Radi, Tan, Prodanov, Evans, & Parks, 1992 ), but accumulation of uric acid can be eliminated by adding uric acid oxidase in industrial production. In future commercial production, the purines in fish sauce and their derived forms like xanthine or uric acid will probably be eliminated by in vitro reconstituted purinolytic enzymes, as demonstrated in our recently published paper ( Shi et al, 2022 ). Some reported that fish sauce is rich in amino acids and small peptides ( Bu et al, 2021 , Lopetcharat et al, 2001 , Wen-yu et al, 2019 ), and other active components ( Pham, Schilling, Yoon, Kamadia, & Marshall, 2008 ), which may have potential inhibitory effects on the xanthine oxidase activity ( Huang et al, 2022 , Zhao et al, 2020 ).…”
Section: Discussionmentioning
confidence: 90%
“…In addition, product inhibition of XOD also has been reported ( Radi, Tan, Prodanov, Evans, & Parks, 1992 ), but accumulation of uric acid can be eliminated by adding uric acid oxidase in industrial production. In future commercial production, the purines in fish sauce and their derived forms like xanthine or uric acid will probably be eliminated by in vitro reconstituted purinolytic enzymes, as demonstrated in our recently published paper ( Shi et al, 2022 ). Some reported that fish sauce is rich in amino acids and small peptides ( Bu et al, 2021 , Lopetcharat et al, 2001 , Wen-yu et al, 2019 ), and other active components ( Pham, Schilling, Yoon, Kamadia, & Marshall, 2008 ), which may have potential inhibitory effects on the xanthine oxidase activity ( Huang et al, 2022 , Zhao et al, 2020 ).…”
Section: Discussionmentioning
confidence: 90%
“…Firstly, UA can be oxidized by UOx to allantoin and H 2 O 2 . The generated allantoin is more easily absorbed and excreted by renal tubules, 37 and the injury caused by H 2 O 2 generation can be attenuated due to the high antioxidant activity of UA, 30,31,38 is further confirmed by the shifted absorption peak of UA with the increasing concentration of H 2 O 2 (Fig. S10, ESI †).…”
Section: In Vitro Drug Release and The Underlying Mechanismmentioning
confidence: 90%
“…Firstly, UA can be oxidized by UOx to allantoin and H2O2. The generated allantoin is more easily absorbed and excreted by renal tubules [37] , and the injury caused by H2O2 generation can be attenuated due to the high antioxidant activity of UA [30,31,38] , which is further confirmed by the shifted absorption peak of UA with the increasing concentration of H2O2 (Figure S10). Afterwards, CaO2 NP is exposed as a high-quality oxygen release reagent, and the generated O2 provides an essential support for the catalytic oxidation of uric acid by UOx.…”
Section: In Vitro Drug Release and Underlying Mechanismmentioning
confidence: 90%